Environmental citizen commitment in the process of territorial transition: Perspectives from the global South - Manel Souidi; Angela Osorio (Territoire en Mouvement)
Territorial transition in southern countries seems to have a distinctive aspect in comparison to northern countries, as it is governed by a dual challenge. On one hand, to regulate unrestrained urbanisation and, on the other hand, to maintain the principles of sustainability promoted on an international scale. In this article, we focus on the interaction between the two main pillars of sustainability, namely the social and the environment, and in particular on the degree of citizen involvement in processes regarding conservation of natural areas within their cities. Therefore, we question the modalities of territorial transition within theoretical and empirical frameworks for the case of the cities of Duitama in Colombia and Setif in Algeria. Two cities situated in southern countries, amid territorial transition, with rather similar geographical and natural characteristics, yet with very different social conditions. Through a comparative study it is possible to comprehend the diversity of social practices towards protecting the environment in these urban areas. The aim of this study is to understand how the inhabitants of these towns are currently involved in environmental protection, and their potential involvement in the ecological transformation that these two territories will undergo in the future.